USE OF PLANT EXTRACTS AS REGULATORS OF QUALITY OF MOMORDIKA FRUIT (MOMORDICA CHARANTIA L.) - O. A. Gribova; N. V. Medvedeva; A. M. Peshkova; V. V. Ivanishchev; V. K. Gins; M. S. Gins (Овощи России, 2016)
Momordica (Momordica charantia L.) is unconventional crop of the Cucurbitaceae family for the central regions of the Russian. Fruits of this crop have anti-inflammatory and immunomodulatory effect. The influence of promising growth regulators from plants on the qualitative composition of fruits momordika has been studied. The positive effect of leaf extract yakon as phytoregulator on productivity increasing and fruit quality of momordika is shown.